Stability Evaluation of Diversion Tunnel Portal Slopes at Lau Simeme Dam Site, Indonesia, using Limit Equilibrium Method - Nurul Huda; I Gde Budi Indrawan; Wahyu Wilopo (Geological Engineering Department Universitas Gadjah Mada, 2022)
Construction of the Lau Simeme Dam used a tunnel as a diversion channel. Slopes at the diversion tunnel portals were prone to failure due to the tunnel excavation and earthquake. Earthquake load was not considered in the designs of the inlet and outlet portal slopes. This research evaluated stability of the tunnel portal slopes under static and earthquake loads using limit equilibrium methods of the Bishop Simplified and Morgenstern-Price. Input material properties for the slope stability analyses were obtained from evaluations of soil and rock cores, including determination of lithology type and rock mass quality based on Geology Strength Index (GSI), and laboratory testing. Evaluations of soil and rock cores indicated that the inlet portal slope consisted of residual soil, good quality tuff breccia, and good quality sandstone. The outlet portal slope consisted of residual soil, poor quality sandstone, poor quality tuff breccia, fair quality sandstone, fair quality tuff breccia, and good quality tuff breccia. The earthquake load coefficient determined by the seismic analyses based on the peak ground acceleration map for 10% probability exceedance in 50 year was 0.125 g. The slope stability analyses showed that the designed inlet and outlet portal slopes were stable under static and earthquake loads. The Bishop Simplified and Morgenstern-Price resulted in relatively similar Fs values. The Fs values of the inlet and outlet portal slopes decreased with the earthquake load application. Although Fs values of the outlet slope under static and earthquake loads met the requirements specified by SNI 8460:2017, the rock mass conditions, particularly the poor rock masses of layers 2 and 3, required special attention. Application of slope reinforcement methods, such as shotcrete, is suggested to further increase the slope stability.